2014
DOI: 10.1200/jop.2013.000903
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Chemotherapy Order Errors With Computerized Physician Order Entry

Abstract: The number of problem- and error-containing chemotherapy orders was reduced sequentially by preprinted order sets and then by CPOE. CPOE is associated with low error rates, but it did not eliminate all errors, and the technology can introduce novel types of errors not seen with traditional handwritten or preprinted orders. Vigilance even with CPOE is still required to avoid patient harm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 11 publications
(10 reference statements)
3
66
2
1
Order By: Relevance
“…This result is congruent with the positive results of other studies that have assessed some EMR functions for cancer care, mainly in improving documentation and standardising procedures in parts of the care process, such as order entry systems, to support the chemotherapy process in medical oncology (Adelson et al, 2014;Brockstein et al, 2011;Harshberger et al, 2011;Kukreti et al, 2014;Levy et al, 2011;Meisenberg et al,2014;Pirnejad et al, 2013) and electronic checklists (record and verify software) in radiation oncology (Albuquerque et al, 2011;Chua et al, 2010;Goldwein, 2011;Kirkpatrick et al, 2013). The users' attitudes, as measured by both the survey and the interviews, were quite positive in the post-period, and the new EMR was considered better than the former system.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This result is congruent with the positive results of other studies that have assessed some EMR functions for cancer care, mainly in improving documentation and standardising procedures in parts of the care process, such as order entry systems, to support the chemotherapy process in medical oncology (Adelson et al, 2014;Brockstein et al, 2011;Harshberger et al, 2011;Kukreti et al, 2014;Levy et al, 2011;Meisenberg et al,2014;Pirnejad et al, 2013) and electronic checklists (record and verify software) in radiation oncology (Albuquerque et al, 2011;Chua et al, 2010;Goldwein, 2011;Kirkpatrick et al, 2013). The users' attitudes, as measured by both the survey and the interviews, were quite positive in the post-period, and the new EMR was considered better than the former system.…”
Section: Discussionsupporting
confidence: 87%
“…But this has rarely been achieved in practice. At the same time, research has found negative unexpected effects resulting from such electronic applications, such as new medication errors (Kukreti et al, 2014;Meisenberg et al, 2014). Only some EMR functions have been tested, such as the order entry systems used to support the chemotherapy process in medical oncology and electronic checklists (record and verify software) in radiation oncology.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction is similar to the reductions described in other articles, even when acknowledging that direct comparisons are not completely possible or they must be made with caution because of the use of heterogeneous methodologies or the use of different antineoplastic ME classifications. International studies show a reduction in MEs from 30·6% to 7% after implementing CPOE for oncohaematological prescriptions . It has also been shown that a CPOE system reduces the risk of prescription errors by 69%, when applied to oral antineoplastic drugs .…”
Section: Resultssupporting
confidence: 80%
“…[10][11][12] Previous surveys from the United States, Canada, and France have found that many cancer centers lack formal procedures or processes for prescribing oral chemotherapy and frequently use hand-written prescriptions. 1,11,13 Establishing prescribing standards and facilitating safe prescribing through use of computerized provider order entry (CPOE) or preprinted orders are first steps in improving the safety of oral chemotherapy.…”
Section: Prescribingmentioning
confidence: 99%
“…10,14-16 The American Society of Clinical Oncology, in collaboration with the Oncology Nursing Society, recently updated its chemotherapy administration safety standards to include recommendations for administration and management of oral chemotherapy, laying out key components of a complete oral chemotherapy prescription. 17 Work in parenteral chemotherapy has demonstrated that use of CPOE systems for chemotherapy prescribing decreases errors, 10 so there has been interest in expanding this tool to oral chemotherapy; however, studies are limited. A group from Rhode Island reported a 69% reduction in prescribing errors after implementation of an enhanced oral chemotherapy CPOE with drug-specific guidelines on prescribing errors within the inpatient environment.…”
Section: Prescribingmentioning
confidence: 99%